CT-Derived Body Composition Values and Complications After Pneumonectomy in Lung Cancer Patients: Time for a Sex-Related Analysis? - Rizzo, Stefania; Petrella, Francesco; Bardoni, Claudia; Bramati, Lorenzo; Cara, Andrea; Mohamed, Shehab; Radice, Davide; Raia, Giorgio; Del Grande, Filippo; Spaggiari, Lorenzo (Frontiers in Oncology, 2022)
Purpose: to assess if CT-derived body composition values and clinical characteristics are associated with the risk of post-surgical complications in men and women who underwent pneumonectomy for lung cancer. Materials and methods: Patients who underwent pneumonectomy between 2004 and 2008 were selected. The Ethics Committee approved this retrospective study with waiver of informed content. Main clinical data collected were: sex; age; weight and height to calculate body mass index (BMI); albumin; C-reactive protein; smoking status; side; sarcopenia; pre-surgical treatments; re-operation; complications within 30 days after pneumonectomy, classified as: lung complications, cardiac complications, other complications, any complication. From an axial CT image at the level of L3, automatic segmentations were performed to calculate skeletal muscle area (SMA), skeletal muscle density, subcutaneous adipose tissue, and visceral adipose tissue. Skeletal muscle index was calculated as SMA/square height. Univariate and multivariate logistic regression analyses were performed to estimate the risk of any complication, both on the total population and in a by sex subgroup analysis. All tests were two-tailed and considered significant at the 5% level. Results: 107 patients (84 males and 23 females) were included. Despite no significant differences in BMI, there were significant differences of body composition values in muscle and adipose tissue parameters between males and females, females being significantly more sarcopenic than males (p=0.002). Separate analyses for males and females showed that age and SMA were significantly associated with post-operative complications in males (p=0.03 and 0.02, respectively). Conclusions: body composition measurements extracted from routine CT may help in predicting complications after pneumonectomy, males and females being different in quantity and distribution of muscle and fat, and males significantly more prone to post-pneumonectomy complications with the increase of age and the decrease of skeletal muscle area.